Fresh Seminal Attributes of Surti Bucks and their Interrelationships - Bhut, Darshita V; Khasatiya, Chandubhai T; Singh, Virendra K; Sharma, Hitendra C (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was conducted to evaluate fresh seminal attributes of Surti bucks and their interrelationships. Fresh semen was collected from four Surti bucks twice a week for 8 weeks, i.e., 64 ejaculates (16/buck). Ejaculates of 4 bucks were pooled and extended with TEYCG extender. Fresh semen was observed pale yellow having mean pH of 6.8. The overall mean semen volume, density, mass activity/ motility, sperm concentration and total sperm count/ejaculate were 0.50±0.02 mL, 3.39±0.08, 3.45±0.09, 4032.81±34.00 millions/mL and 1986.25±86.03 million, respectively. Percentages of individual sperm motility, live sperms, abnormal sperms and HOST reacted sperms in pooled extended Surti bucks semen were 80.63±1.76, 83.06±1.64, 9.56±0.47 and 78.06±0.96. Ejaculate volume and total sperm count significantly (p<0.05) varied between bucks. Moreover, significant correlations were observed for volume with density (-0.281), sperm concentration (-0.247) and total sperm count (0.975) as well as density with sperm concentration (0.247) and total sperm count (-0.260). The coefficient of variation was minimum for sperm concentration and maximum for total sperm count. In pooled and extended semen, individual sperm motility was significantly and positively correlated only with live sperms % (r=0.899). The coefficient of variation (%) was highest for abnormal sperms and lowest for HOST reacted sperms. Conclusively the study established normal values of fresh semen of Surti bucks and their interrelationships.